You Don't Have to Be Evil to Work Here, But it Helps - Holt, Tom, 1961- (London Orbit Books, 2006)
Colin Hollinghead is a young man going nowhere fast. Working for his dad might have seemed like a good idea at the time, but starting at the bottom in the widget-making industry has somehow lost its appeal. And now the business is in trouble. At least his father has a plan to turn things round - a new work force that will improve profit margins and secure the company's future for eternity. The deal looks great on paper, but they do say that the devil is in the detail - and the old rogue certainly seems to be involved in some capacity. Colin needs help. Perhaps his new friend from J.W. Wells & Co. (Practical and Effective Magicians, Sorcerers and Supernatural Consultants) can help.
Keywords: Magic -- Family-owned business enterprises -- Magicians